Plan de negocio para la creación de una empresa de barras móviles para eventos sociales en la ciudad de Quito - Chávez Villacreses, Sofía Nathaly (2016)
This research proposes a business plan, which is aimed at the feasibility study for the creation of a company dedicated to offer service mobile bar serving drinks and cocktails for social and corporate events in the city of Quito. The proposed specific objectives guided the realization of a market study that identified tastes and preferences of the target customer to design a creative proposal. Similarly, a functional organic structure practice to meet generating activities set value. Finally, a financial study that determined the feasibility of implementing the business was done, and this cost effective, flexible and attractive. The methodology used was based on the descriptive method combining qualitative and quantitative studies. The first focused on determining customer consumption characteristics necessary to formulate competitive strategies. The second possible to establish expected revenue projections, evaluating the business defining its capacity and performance. As for the results, these were expressed in five chapters where the target market is segmented, knowing the acceptance of the service and processes required for effective delivery settled. business strategies that will achieve an effective positioning, which will be prioritized to have a wide variety of service options bar both in design and in cocktails and drinks offered were raised. Thus, it is expected to reach a position that meets the budgets formulated, achieving a positive return with broad prospects for growth. To minimize the risks of introducing the service, strategic planning objectives established short, medium and long term, in which it is proposed to have strategic alliances with companies that organize events that allow them to be identified on the market. Once the desired position is reached is expected to start a national expansion with a sustained and sustainable business over time arises. Its implementation represents a contribution to the national economy, proposing innovative activities that raise the quality of upcoming events and facilitate their organization, generating direct and indirect employment sources.